Is manufacturing the silver bullet engine of growth for South Africa? - Nongalo, Philiswa (Graduate School of Business (GSB), 2026)
This research paper is inspired by the developing country trap of South Africa, evidenced by over a decade of high inequality, high unemployment and stagnating economic growth. At the peak of industrialisation developed countries sustained economic growth, while developing countries experienced pathological premature de-industrialisation marked by economies that fail to realise their full potential resource utilisation, employment and growth. The Kaldorian framework established the manufacturing sector as serving a critical role in inducing sustainable growth of the economy. This framework articulated the manufacturing sector's dynamism and tradability, positioning it ahead of other sectors to drive their growth and facilitate intersectoral relationships. In addition, the success of the South Asian economy propelled by modern Information and Communication Technology (ICT) services-led growth has inspired a debate on the services sector as an alternative to manufacturing engine of growth. Within this context, this research examines re-industrialisation of the economy as a means to attain rapid growth. The research also examined value added and labour productivity (LP) growth per sector from 1991 to 2021, which are proxies of economic performance. Using the vector autoregression (VAR) multivariate ordinary least squares (OLS) model, the Granger causality was examined to test for intersectoral relationships amongst the sectors. Contrary to Kaldor's theory of the growth pulling effect of the manufacturing sector (Kaldor,1966,1968), the data analysis suggested that the manufacturing sector does not Granger cause growth of other sectors. Instead, a unidirectional relationship was observed wherein the growth in value of services and agriculture Granger cause manufacturing. Additionally, productivity in services, agriculture and the non-manufacturing Granger cause the LP of the manufacturing sector. The bidirectional relationship between the manufacturing sector and the services sector, confirmed by research on the export of intermediate goods, forms a strong evidence basis for the implementation of a targeted multi sub-sector investment policy. Moreover, long-term equilibrium was established for value added and LP growth per sector. The findings showed that manufacturing share of employment drives an increase in gross private savings (GPS) and TFP in the long term. Insignificant impact in the short term for total factor productivity (TFP) was observed. In the long term, periodic convergence to equilibrium for the GPS was observed, while a stable long-run relationship was established for TFP.